KNOWLEDGE AND INFORMATION - FACTORS OF ECONOMICAL AND SOCIAL DEVELOPMEN - ANDRA GANCIOV (MICULESCU); LOREDANA IOANA PRIBAC (Annals of the University of Petrosani: Economics)
This work develops a view over the more and more important role that knowledge and information begin to play in all the aspects of life. Also, the work analyses the concepts of economy based on knowledge and informational society, with the implications and links between them, regarded from several economic perspectives. The conclusion reached is that nowadays' society is in a continuous transformation and that without information and knowledge one cannot cope with the progress of humankind, and the society of knowledge and the informational society are factors of globalization, which will give a new configuration to economy.